PENDIDIKAN PESANTREN SEBAGAI TRANSFORMASI SOSIAL DI LEMBAGA PENDIDIKAN ISLAM MAKTAB NUBDZATUL BAYAN (MAKTUBA) AL-MAJIDIYAH PAMEKASAN - Syafrawi, Syafrawi (Universitas Islam Madura, 2017)
Patterns and change management as well as the improvement of educational management schools are the decisive factors for the success of the education program. So that schools as social transformation necessary to hold a perfection as was done by LPI Maktuba Al-Majidiyah which include 1) use old patterns and new patterns, 2) there is no conflict with the dynamics of social change society, 3) adjust to the social needs are growing day more advanced, 4) set up a pattern of education which is matched with the social state of today's society. There are some obstacles encountered in the implementation of Islamic boarding schools as a social transformation in LPI Maktuba Al-Majidiyah is a) internal and external constraints, b) the infrastructure Constraints , c) the intelligent of human resource Constraints, d) Constraints of cooperation with guardians of students sometimes they disobey. There are some the steps is taken to overcome the obstacles faced in educational boarding school as a social transformation in LPI Maktuba Al-Majidiyah is a) Conduct the evaluation of education programs on a regular basis, or even incidental to rely requirement, b) Attempts to complement the educational facilities that are likely to support the implementation of educational activities, c) Conducting PBM adapted to the circumstances and the ability of the child or learner, d) Conducting socialization to the guardians of students so that they support and do not disobey the regulation that have been agreed upon agency.